2019
DOI: 10.30621/jbachs.2019.555
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids in Our Foods: A Short Review

Abstract: The aerobic metabolism in biological systems, produces reactive oxygen species (ROS) known as prooxidants even in basal conditions. If the formation of prooxidants increases, it leads to oxidative stress/damage. Various diseases in humans (cancer, chronic diseases, cardiovascular problems etc.) accompanies with prooxidant damage. Endogenous and exogenous antioxidants protect biomolecules against the damage of prooxidants. Flavonoids are potent antioxidant molecules, which scavenge free radicals in vitro. They … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 43 publications
2
28
0
5
Order By: Relevance
“…e content of apigenin in fresh foods, especially vegetables and herbs [45], oscillated from 0.10 to 0.54 mg/kg of fw and these values are comparable to the levels observed in this study. e content of apigenin presented in fresh parsley [45] was at the exceptional level of 21.6 mg/kg of fw.…”
Section: Quantitative Analysis Of Individual Phenolic Compounds In Salaksupporting
confidence: 89%
“…e content of apigenin in fresh foods, especially vegetables and herbs [45], oscillated from 0.10 to 0.54 mg/kg of fw and these values are comparable to the levels observed in this study. e content of apigenin presented in fresh parsley [45] was at the exceptional level of 21.6 mg/kg of fw.…”
Section: Quantitative Analysis Of Individual Phenolic Compounds In Salaksupporting
confidence: 89%
“…When comparing the obtained results with those reported in the literature, it was observed that Brassica plants, such as broccoli and watercress, presented much lower flavonoid contents than those obtained by Agarwal et al [49] (broccoli, 13.98 mg QE/g vegetable) and Aires et al [50] (watercress, 5.6 mg CatE/g dried weight). This difference may be associated with some factors, such as geographic variation, harvest time, and environmental and agronomic conditions [51,52].…”
Section: Determination Of the Phytochemical Compositionmentioning
confidence: 99%
“…Flavonoids are one of the most important and studied phenolic compounds. These phytochemicals are plant secondary metabolites and are widely found in different food matrices, such as fruits, vegetables and certain beverages [199]. In the last years, flavonoids have been described as related to several favorable biochemical and antioxidant effects, such as, among the others, those associated with cancer, Alzheimer's disease, diabetes, and atherosclerosis [200,201].…”
Section: Flavonoidsmentioning
confidence: 99%